The new characters of literature: gangs as historical subjects in Central American narrative - Pérez Viana, Gerardo Alexis (LETRAS, 2023)
This research was conducted from the thematic perspective on the phenomenon of gangs as a common trend in different narrative segments of Central American literature. The novel Yurique (2019) by Berne Ayalá, the short story El sueño (2022) by Josué Andrés Moz, the short story Hombre de rodillas from the book La teta mala (2019) by Mauricio Orellana Suárez, and the short story La Doña from the book El Domador (2003) by Javier Vindel are studied. The category system for ‘maro-poetics’ articulated by Jorge Martínez López and Vladimir Flores Ascencio was used: the "clandestine-cartographic chronotope" and the "historical-personal chronotope" to segment those particles belonging to the visceral topic of gangs. On the other hand, the "character" category proposed by Francisco Álamo Felices was adopted. All the theoretical bases help to determine a new aspect called "maro- narrative", in which the characters assume the main role of witness or victim.